The Power of Palaeocurrents: Reconstructing the Palaeogeography and Sediment Flux Patterns of the Miocene Sandakan Formation in Eastern Sabah - Jon Noad (Berita Sedimentologi, 2013)
Up until now the use of palaeocurrents as a primary tool in establishing regional palaeogeography and sediment dispersal patterns in the ancient has been limited. An outcrop study on the Miocene Sandakan Formation in eastern Sabah identified five facies belts, subdivided on the basis of sedimentological and palaeontological data. More than 140 outcrop sections were measured over an area covering approximately 200 square kilometres. The facies were interpreted to have been deposited in settings ranging from ancient mangrove deposits through shoreface sediments and out into the open marine.More than 200 palaeocurrent readings taken on these facies allowed a clear picture to be built up of the sediment dispersion patterns across the palaeo-Sandakan Basin, passing from northward directed flow through mangrove channels into a longshore drift dominated shallow marine, coastal shelf. This gave way northwards to a storm dominated belt of tempestite deposits cut by rip current channels. Flow through these channels, driven by frequent storms, was northward directed. Further to the north more quiescent, open marine, muddy conditions prevailed. A sediment budget can be estimated using the sand fraction of the various lithofacies identified during the study.